Manejo Agronómico del cultivo de Jengibre (Zingiber officinale) y sus procesos agroindustriales - Salazar Mera, Juan José (2022)
This document refers to the agronomic management of the cultivation of Ginger (Zingiber officinale) and its agro-industrial processes. It is necessary for farmers to carry out good agronomic management of the crop so that yields are improved and therefore they obtain economic benefits by offering a good quality product for the industrialization process. From the above, it is concluded that in scientific and field research it was possible to know that ginger can be obtained in different presentations that help in the elaboration of different recipes; The production of ginger and its transformation into added value is important, knowing that in Ecuador there are several cultivation areas that meet favorable conditions and that would allow obtaining a quality root suitable for being processed into derivatives such as tea, essences, oils, beer. , dust and others; ginger can be found and consumed in a variety of culinary preparations such as: infusions, breads and pastries. As a flavoring agent for sauces, rice dishes, soups, meat and fish; it is used as a raw material for the manufacture of more complex semi-synthetic drugs, the chemical structure of its active ingredients can serve as a model for the production of synthetic drugs and such principles can be used as taxonomic markers in the search for new drugs; Ginger is available for export in two presentations: Young Ginger, also known as spring ginger, is very mild and less pungent than mature ginger. Ripe ginger has a well-formed skin that preserves a sweet and very spicy flavor and aroma. Since ancient times, this medicinal plant has been used for vertigo, nausea and travel sickness, circulatory and blood supply disorders, muscle pain and spasms, as well as for gastric and digestive disorders, being considered an aphrodisiac.